Case report: An innovative non-invasive technique to manage shell injuries in C. carbonarius - Horvath-Pereira, Bianca de Oliveira; Paulini, Fernanda; Sotelo, Marco Olívio; Leardini, Ettore Giovanni; Tavares, Dhiego Cristiano; Almeida, Gustavo Henrique Doná Rodrigues; da Silva Júnior, Leandro Norberto; Pinho, Letícia Beatriz Mazo; Miglino, Maria Angelica; Araujo, Michelle Silva (Frontiers in Veterinary Science, 2022)
Shell fractures are one of the most traumatic and recurrent injuries observed in chelonians during clinical practice. The most common causes of fractures are falling, being run over by automobiles, being burned, and wild animal bites. Epoxy, acrylic resin, polyester, fiber-grass blanket and screw fixation are among the current techniques used to treat fractures. Regarding the difficulty of fracture repair in the carapace, this case report aimed to report a procedure that is effective, less time consuming, accessible, affordable, and safe for shell fractures in C. carbonarius. During the physical examination, the animal showed two fractures, in the dorsal region of the carapace and right lateral side of the bridge, with subcutaneous tissue exposure and loss of a small piece of dorsocranial carapace. To treat these injuries, the animal was submitted to a resin application. It was observed that the treatment was effective, presenting reduction of the fracture. A month after the procedure, the animal showed no intercurrence. This resin proved to be an innovative and promising alternative wa to treat fractures, suggesting the development of new non-invasive approaches for several tissues and different animal species.